The Role of Forensic Accounting in Reducing Financial Corruption : from the point of view of External Auditors and Forensic Accountants (Economic studies journal, 2019)
The study aimed to know the role of forensic accounting in reducing financial corruption from the point of view of external auditors and forensic accountants in the city of Sirte (Libya) by studying the relationship between the following variables: ( fields and procedures of forensic accounting, the knowledge and skills of the forensic accountant, the scientific and practical qualification of the forensic accountant ), The study relied on a descriptive analytical approach through the design of a questionnaire distributed to the sample of the study, which consisted of external auditors, staffs of Audit Bureau and forensic accountants in the city of Sirte. A number of statistical methods were used in this study, the most important of which were mean, standard deviations, relative weight, Cronbach's alpha test and Pearson correlation coefficient, and the most important findings of the study: There is a positive role for forensic accounting in reducing financial corruption.
Keywords: Accounting; Forensic; Corruption; Financial; Auditors